b (: c)
Introduction of Basic Rights of People in Afghanistan.
369
Keywords: Criminal law -- Afghanistan; Family Law -- Afghanistan; Property -- Afghanistan; Right of property -- Afghanistan; Inheritance and succession -- Afghanistan